So long Marianne [videorecording (DVD)] - Moffat, Robbie, 1954-; Gallagher, Dop Lee; Baxter, Marnie; Gates, Jon-Paul; Arnold, Sean (Actor); Rath, Rachel (Leomark Studios, 2023)
Poet and novelist Leonard Cohen travels to Hydra to rewrite his novel. After some time on the island he finds the love of his life Marianne, with her encouragement he sings his poetry becoming the singer the world knows today.